(untitled) (New York, 1990)
This volume 4 begins with Micromechanisms of Fracture Modes and goes through Polymeric Extrusion. The concluding volume will have a complete index of the entire work. When all six volumes are complete, this will be the first A-Z encyclopedia of composites.
Keywords: Composite materials,Vật liệu hỗn hợp; Dictionaries,Từ điển